1985
DOI: 10.3168/jds.s0022-0302(85)81110-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Morantel Tartrate in a Sustained Release Bolus on the Control of Subclinical Gastrointestinal Parasitism in First-Year Grazing Dairy Replacements

Abstract: Thirty-four heifers (24 Holstein, 8 Ayrshire, 2 Jersey) and 12 Holstein steer calves were grouped into 23 blocks of 2 animals each according to breed, sex, and body weight. Animals in each block were randomly assigned to control or treated groups. The treated group received an anthelmintic bolus containing morantel tartrate before they were permitted access to pasture. A 2.6 ha pasture was divided in half with a double fence; the resulting two pastures had separate feed and water troughs. Steer calves were sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Current literature concerning the treatment of replacement heifers with an anthelmintic has produced contradictory results. Block et al (1985) found heifers treated with morantel tartate had increased weight gain and decreased days to conception. Additionally, Zajac et al (1991) found no difference in final conception rates in heifers developed on pasture that were treated with ivermectin at weaning.…”
Section: Discussionmentioning
confidence: 97%
“…Current literature concerning the treatment of replacement heifers with an anthelmintic has produced contradictory results. Block et al (1985) found heifers treated with morantel tartate had increased weight gain and decreased days to conception. Additionally, Zajac et al (1991) found no difference in final conception rates in heifers developed on pasture that were treated with ivermectin at weaning.…”
Section: Discussionmentioning
confidence: 97%
“…One of the most widespread Beef, Cows, health problems for ruminants on a worldwide basis is the presence of internal parasites (Armour, 1980;Borgsteede and Burg, 1982). The level of infection and its effect on animal performance in the U.S. and Canada has been documented in certain areas by numerous researchers, including Levine and Aves (1956); Zimmerman and Hubbard (1961); Cox and Todd (1962); Jacobson and Worley (1 969); Ferguson et al (1971); Leland et al (1973); Ciordia (1975); Ward et al (1979); Wescott et al (1979); Baker et al (1981); Block et al (1985);Kuhl et al (1985, andKnox (1989).…”
Section: Introductionmentioning
confidence: 96%